2017
DOI: 10.1021/acs.jpclett.7b00473
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Molecular Dynamics Simulations of Gram-Negative Bacterial Cell Envelopes

Abstract: Bacteria are protected by complex molecular architectures known as the cell envelope. The cell envelope is composed of regions with distinct chemical compositions and physical properties; namely membranes and a cell wall. To develop novel antibiotics to combat pathogenic bacteria, molecular level knowledge of the structure, dynamics and interplay between the chemical components of the cell envelope that surrounds bacterial cells is imperative. In addition, conserved molecular patterns associated with the bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…To this end, it was assumed that the permeation across the asymmetric OM is comparable to or smaller than that across symmetric membranes because of the presence of lipopolysaccharides in the outer leaflet of the asymmetric bilayer. Especially on the computational side, quite some effort has been made recently to be able to describe asymmetric membranes in atomic detail and to study translocation of ions and substrates through proteins embedded therein (17,18,(65)(66)(67). As already mentioned in the introduction, for the development of new antimicrobial treatments, it is of prime importance to better understand the transport across the OM of Gram-negative bacteria (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, it was assumed that the permeation across the asymmetric OM is comparable to or smaller than that across symmetric membranes because of the presence of lipopolysaccharides in the outer leaflet of the asymmetric bilayer. Especially on the computational side, quite some effort has been made recently to be able to describe asymmetric membranes in atomic detail and to study translocation of ions and substrates through proteins embedded therein (17,18,(65)(66)(67). As already mentioned in the introduction, for the development of new antimicrobial treatments, it is of prime importance to better understand the transport across the OM of Gram-negative bacteria (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the transport of antibiotic molecules, especially across the OM of Gram-negative bacteria, has been identified as one of the key problems in antibiotics research (14)(15)(16). Recently, considerable effort-both experimentally as well as theoretically-has been put into this subject (see, for example, (17)(18)(19)(20)(21)(22)(23)(24)(25)), which is quite complex, partially because of the large diversity of channels and the so far often-incomplete knowledge of their structure and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…LPS models have been parameterized for all major families of molecular dynamics (MD) force fields, [23][24][25][26][27][28] and outer membrane simulations with LPS are increasingly more common. [29][30][31][32][33] However, the performance of common ion force fields with these LPS models has rarely been evaluated, and inconsistencies exist between different parameterizations. The…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Recent simulations have also membrane proteins and the LPS. [45][46][47] It has been shown that fully hydrated mixed lipid charged bilayers made of phosphatidylethanolamine (POPE) and phosphatidylglycerol (POPG) in the proportion 3:1 and counterions are stable and can serve as a suitable model of the inner bacterial membrane. 48 In the present study, bacterial membranes were built using the CHARMM-GUI online server 49 in two sizes: 1) To study PHMB polymer-bilayer systems, the bilayer consisted of 192 POPE and 64 POPG lipids (structures are provided in Figure S2) in each leaflet (total of 512 lipids), and 2) the bilayer for the PHMB dimer-bilayer system had 48 POPE and 16 POPG lipids in each leaflet (total of 128 lipids).…”
Section: Bilayer and Phmb Systemsmentioning
confidence: 99%